Remarkable response with pembrolizumab plus albumin-bound paclitaxel in 2 cases of HER2-positive metastatic breast cancer who have failed to multi-anti-HER2 targeted therapy. Issue 4 (3rd April 2018) - Li, Bian; Tao, Wang; Shao-hua, Zhang; Ze-rui, Qu; Fu-quan, Jin; Fan, Li; Ze-fei, Jiang
ABSTRACT: In clinical practice, one subgroup patients of breast cancer might have developed resistance to multi-anti-HER2 targeted drugs(trastuzumab, lapatinib and/or T-DM1) and can not benefit from the anti-HER2 targeted therapy continuously. We attempt to change the next therapic way for these patients. Two patients with metastatic breast cancer who have failed to multi-anti-HER2 targeted therapy were treated with pembrolizumab (2 mg/Kg, day1) plus albumin-bound paclitaxel (125 mg/m 2, day1, 8) every 3 weeks. CT evaluation and HER2 ECD test were performed every 2 cycles. Both of the two patients achieved remarkable response with Partial Remission (PR), meanwhile serum HER2 ECD levels (the upper normal limit is 15 ng/ml) showed a remarkable decreases(compared to the base line decreases 75% and 60% respectively). The results indicate that regimen of pembrolizumab combination with albumin-bound paclitaxel might produce response in patients with HER2-positive metastatic breast cancer who have failed to multi-anti-HER2 targeted therapy.